2010
DOI: 10.1179/016164110x12767786356598
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine reactivity in cerebral vessels after severe traumatic brain injury

Abstract: Objectives Traumatic brain injury (TBI) causes an early reduction of cerebral blood flow (CBF). The purpose was to study cerebrovascular endothelial function by examining the reactivity of cerebral vessels to L-arginine. Methods Fifty-one patients with severe TBI were prospectively studied by measuring cerebral hemodynamics before and after the administration of L-arginine, 300 mg/kg at 12 hrs and at 48 hrs after injury. These hemodynamic measurements, using transcranial Doppler techniques, included internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…During the early phase, a period of relative deficiency in NO and a low level of CBF, the administration of l -arginine has been shown to improve CBF and neurological outcome in models of TBI ( 34 ). Administration of l -arginine in patients after severe TBI induced an increase in internal carotid artery flow volume, which was larger at 48 h than at 12 h, and tended to be larger in the less injured hemisphere at both time periods, suggesting that dysfunction of cerebrovascular endothelium plays a role in the reduced CBF observed after TBI ( 40 ). Some of the variability in patient outcome that occurs following severe TBI may result from eNOS polymorphisms ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the early phase, a period of relative deficiency in NO and a low level of CBF, the administration of l -arginine has been shown to improve CBF and neurological outcome in models of TBI ( 34 ). Administration of l -arginine in patients after severe TBI induced an increase in internal carotid artery flow volume, which was larger at 48 h than at 12 h, and tended to be larger in the less injured hemisphere at both time periods, suggesting that dysfunction of cerebrovascular endothelium plays a role in the reduced CBF observed after TBI ( 40 ). Some of the variability in patient outcome that occurs following severe TBI may result from eNOS polymorphisms ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, to test the contribution of BH 4 depletion to eNOS uncoupling, we treated arteries with the pterin salvage pathwayderived precursor l-sepiapterin (1 lM). l-sepiapterin partially restored vasodilation induced by ACh; although the EC 50 was not affected, the maximal dilation induced by 1 lM ACh in the presence of l-sepiapterin was improved and reached approximately 90% of control levels ( Fig. 5 and Table 1).…”
Section: Arginase Inhibition and Exogenous Supplementation Of Bh 4 Ormentioning
confidence: 92%
“…47,48 Although these observations would seem to suggest l-arginine supplementation as a therapeutic strategy, several studies have shown that l-arginine reactivity varies depending on time point after injury, vascular bed, and species studied, age, and the underlying disease. [48][49][50][51][52][53] One of the limitations of our study is that we focused on a specific time point after injury. Additional studies are needed to address the longitudinal course of vascular responses including earlier times after TBI and later time points after clinical recovery.…”
Section: Fig 7 Total Arginase Activity Is Increased After Traumaticmentioning
confidence: 99%
“…There was also a significant direct relationship between the concentration of NO metabolites and regional CBF [ 142 ]. In severe TBI patients, l -arginine administration at 48 h post-injury had a better response in improving internal carotid artery flow volume than at 12 h following brain injury [ 143 ]. The above findings further emphasize the importance of determining the effective therapeutic window for drug administration following brain injury.…”
Section: Oxidative Stressmentioning
confidence: 99%